BS ISO 20816-3. Mechanical vibration. Measurement and evaluation of machine vibration. Part 3. Industrial machinery with a power rating above 15 kW and operating speeds between 120 min-1 and 30 000 min-1 (9th August 2021) - British Standards Institution,
No abstract available